2015
DOI: 10.1159/000441624
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Smoking Are Associated with Future Development of Advanced Chronic Kidney Disease in Older Adults

Abstract: Introduction: Metabolic syndrome (MetS) and smoking have been identified as risk factors for chronic kidney disease (CKD) in cross-sectional studies in various age groups, but longitudinal data on progression of CKD in older adults are limited. Our objectives were to examine whether MetS and its components and smoking predict the onset of CKD stage 3b (CKD-3b) in older adults. Methods: A subset of participants of the Einstein Aging Study who were free of diabetes, dementia, and CKD-3b at enrollment were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Subjects with stage 3a (GFR 45–59 mL/min/1.73 m 2 ) have less risk of vascular complication and mortality compared with the 3b group [26]. Zammit et al suggested that MetS is associated with an increased incidence of stage 3b [27]. Kim analyzed 2,624 Korean adults aged ≥ 50 years and found that serum concentrations of 25(OH)D were significantly lower in subjects with MetS than in those without MetS [10].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with stage 3a (GFR 45–59 mL/min/1.73 m 2 ) have less risk of vascular complication and mortality compared with the 3b group [26]. Zammit et al suggested that MetS is associated with an increased incidence of stage 3b [27]. Kim analyzed 2,624 Korean adults aged ≥ 50 years and found that serum concentrations of 25(OH)D were significantly lower in subjects with MetS than in those without MetS [10].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is a strong, modifiable risk factor for CVD (as well as other adverse health outcomes such as lung disease and cancer); smoking may also cause direct renal damage through microvascular injury and promotion of atherosclerosis, and has been associated with CKD in the general population. 268 , 269 A recent meta-analysis based on data from nearly 5 million persons identified from 7 general population cohorts found that, compared with nonsmokers over median cohort follow-up of 4 to 16 years, current smokers had a 76% increase in the risk of ESKD (adjusted HR, 1.29 1.76 2.41 ) and past smokers had a 45% increase in risk (adjusted HR, 1.23 1.45 1.71 ). 7 After calibration to annual ESKD incidence in the US healthy population, variations in the projected 15-year and lifetime risks of ESKD based on smoking status were generated according to age, sex, and race for healthy persons (assuming age-specific GFR, urine ACR 4 mg/g [0.4 mg/mmol], SBP 120 mmHg, BMI 26 kg/m 2 , and absence of diabetes mellitus; Figures 20 and 21 ).…”
Section: Rationalementioning
confidence: 99%
“…Considering this, there are data suggesting that the presence of obesity (BMI >30) paradoxically confers a survival advantage in ESRD rather than being a risk factor for cardiovascular disease morbidity and mortality in this population [46]. Further, there are a number of population studies that indicate that a lower BMI (<25) is a consistently strong predictor of increased mortality, a relationship that is lost at higher BMIs [47,48,49,50,51]. It is thought there may be significant residual confounding in these studies due to unmeasurable variables such as the lack of time-dependent assessment of nutritional indices, progressive malnutrition, protein energy wasting, uremic conditions, or the presence of residual renal function in the end-stage kidney that cannot be accounted for in these population-level studies.…”
Section: What Is the Role Of Obesity In Ckd/esrd Separate From That Omentioning
confidence: 99%